Current Insights Into the Pathology of Canine Intervertebral Disc Extrusion-Induced Spinal Cord Injury - Spitzbarth, Ingo; Moore, Sarah A.; Stein, Veronika M.; Levine, Jonathan M.; Kühl, Bianca; Gerhauser, Ingo; Baumgärtner, Wolfgang; , The Canine Spinal Cord Injury Consortium (CANSORT-SCI); Moore, Sarah A.; Olby, Natasha J.; Gjessing, Kady M.; Davidson, Rhanna M.; et al. (Frontiers in Veterinary Science, 2020)
Spinal cord injury (SCI) in dogs is commonly attributed to intervertebral disc extrusion (IVDE). Over the past years substantial progress has been made in the elucidation of factors contributing to the pathogenesis of this common canine disease. A detailed understanding of the underlying histopathological and molecular alterations in the lesioned spinal cord represents a prerequisite to translate knowledge on the time course of secondary injury processes into the clinical setting. This review summarizes the current state of knowledge of the underlying pathology of canine IVDE-related SCI. Pathological alterations in the spinal cord of dogs affected by IVDE-related SCI include early and persisting axonal damage and glial responses, dominated by phagocytic microglia/macrophages. These processes are paralleled by a pro-inflammatory microenvironment with dysregulation of cytokines and matrix metalloproteinases within the spinal cord. These data mirror findings from a clinical and therapeutic perspective and can be used to identify biomarkers that are able to more precisely predict the clinical outcome. The pathogenesis of progressive myelomalacia, a devastating complication of SCI in dogs, is not understood in detail so far; however, a fulminant and exaggerating secondary injury response with massive reactive oxygen species formation seems to be involved in this unique neuropathological entity. There are substantial gaps in the knowledge of pathological changes in IVDE with respect to more advanced and chronic lesions and the potential involvement of demyelination. Moreover, the role of microglia/macrophage polarization in IVDE-related SCI still remains to be investigated. A close collaboration of clinical neurologists and veterinary pathologists will help to facilitate an integrative approach to a more detailed understanding of the molecular pathogenesis of canine IVDE and thus to identify therapeutic targets.